A rare case of recurrent cerebrospinal fluid rhinorrhea - Karthikeyan, Ramalakshmi; Rashid, Rahim A. (International Journal of Research in Medical Sciences, 2023)
Cerebrospinal fluid (CSF) rhinorrhea is the leakage of cerebrospinal fluid through the nostrils due to an abnormal communication between the nasal cavity and sub–arachnoid space. CSF rhinorrhoea can be traumatic or spontaneous. CSF rhinorrhea carries a risk of ascending infection leading to meningitis. CSF rhinorrhea is not very common and could be easily mistaken for rhinitis. Physicians need to have a high index of suspicion to diagnose and treat this rare and potentially serious condition. Here we discuss a case of delayed post-traumatic CSF rhinorrhea -an unusual presentation in a primary care setting, focusing on presentation and diagnosis.